The Mathematics and Topology of Fullerenes - Cataldo, Franco; Graovac, Ante; Ori, Ottorino (Carbon Materials: Chemistry and Physics,, 2011)
Mathematics and Topology of Fullerenes presents a comprehensive overview of scientific and technical innovations in theoretical and experimental studies. Topics included in this multi-author volume include: Clar structures for conjugated nanostructures; counting polynomials of fullerenes; topological indices of fullerenes; the wiener index of nanotubes; toroidal fullerenes and nanostars;  C60 Structural relatives: a topological study; local combinatorial characterization of fullerenes; computation of selected topological indices of C60 and C80 Fullerenes via the Gap Program; 4valent- analogues of fullerenes; a  detailed atlas of Kekule structures of C60.   This multi-author volume is targeted at advanced graduates and researchers working in carbon materials, chemistry and physics.